STUDY TO INVESTIGATE THE ANXIOLYTIC EFFECT OF RUBIA CORDIFOLIA LINN IN MICE - CHAUHAN, ANKUSH; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2025)
Objective: To evaluate anxiolytic activity of extracts of Rubia cordifolia in albino mice by using Actophotometer (locomotor activity), Elevated Zero maze, Mirrored Chamber and biochemical estimation like estimation of plasma corticosterone levels. Methods: Healthy, Swiss Albino mice weighing 20-35 g and aged 6-8 w were maintained under standard laboratory conditions with controlled temperature (25±2 °C), humidity (40±10 %) and 12 h light and dark cycles each. The animals were fed with standards rodent pellet diet and water ad libitum. Rubia cordifolia extract will be administered p. o.. to mice daily in two different doses (300 and 600 mg/kg/p. o.) for 14 d. All the animals will be evaluated for behavioral parameters, i. e. Actophotometer (locomotor activity), Elevated Zero maze, Mirrored Chamber and biochemical estimation like estimation of plasma corticosterone levels will be performed. Results: In the present study, we have undertaken the anxiolytic activity of extracts of Rubia cordifolia in Swiss albino mice, at the dose of (300 and 600 mg/kg/p. o.) with oral administration respectively. Conclusion: In conclusion extracts of Rubia cordifolia have shown significant results as anxiolytic activity using locomotor activity), Elevated Zero maze, Mirrored Chamber.